Upaya Pemilik Bisnis dalam Mempertahanan dan Membuktikan Rahasia Dagang Jika Terjadi Pelanggaran - Della Syahputri; Fatimah Ratu Azzahra; Shantika Vidia A. Z; M Raihan; Vipta Adji Prestianto; Zahra Rahmah Fadilah; Mustaqim M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research employs a normative approach to identify, explain, and accurately describe the laws and regulations related to trade secret protection. The primary focus of this research is on business owners' efforts to maintain the confidentiality of their trade secrets and how to prove the existence of trade secrets in cases of infringement that need resolution in court. By analyzing legal aspects and relevant regulations, this research provides practical guidance for business owners and legal professionals in understanding and managing their trade secrets. This research offers valuable insights into trade secret protection and its legal implications in modern business, as well as highlighting key issues related to trade secret owners' rights and dispute resolution mechanisms concerning trade secrets.